Virtual learning in primary education: Roducate learning app and pupils’ English language outcomes in Ondo State, Nigeria - Emmanuel, Isaac Friday (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
In today’s rapidly evolving digital world, technologies remain essential to modern challenges. However, in Nigeria, these technologies have not gained the prominence they deserve, especially at the primary school level. This study examined the effectiveness of Roducate in Primary School Pupils’ English Language Outcomes in Ondo State, Nigeria. Three research questions were answered and two hypotheses were tested. A quasi-experimental and descriptive survey research design were adopted for the study. The population consisted of all primary school pupils and their teachers. Through purposive sampling, 45 pupils and 30 primary school teachers were selected. Pupils with access to mobile devices were placed in the experimental group and those without access on the control group. The research instruments were the Teachers’ Roducate Knowledge Questionnaire (TRKQ), r = 0.76, Level of Digital Competence Questionnaire (LDCQ), r = 0.79, and the Primary School Common Entrance Past Questions. Findings revealed that Roducate has a significant effect on pupils’ achievement in English language. Similarly, primary school teachers do not know about Roducate learning app. On the basis of these findings, the study recommends that there should be comprehensive teacher training programs focusing on building digital competence for primary school teachers.